The Development of Mathematics Module Based on the Contextual Apporach in Algebraic Forms Material - Fitriani Nur; Nurpaidah Nurpaidah; Suharti Suharti; Sri Sulasteri; Thamrin Tayeb (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
The purpose of this study was to analyze the process and results of developing a mathematics module based on the contextual approach in algebraic forms which was valid, effective, and practical in the VII grade of Junior High School. This study was research and development (R&D) adapted from the ADDIE development model. The product developed was a mathematics module containing algebraic form materials based on the contextual approach, the subject of the study were students of junior high school. Data collection techniques in this study were validation sheets, questionnaires, learning outcomes tests, and observation sheets. The data analysis technique used was descriptive data analysis. Based on the research findings, it was found that the process of developing teaching materials in this study using the ADDIE instructional development model included five stages, namely analysis, design, development, implementation, and evaluation. The mathematics module has met the criteria of validity, effectiveness, and practicality, which means that this module is suitable to be applied in the interaction of teaching and learning activities. The developed module to optimize students understanding of concepts and be able to make students more focus on the learning process in the classroom.